Dark Victory - Joyce, Brenda (Don Mills, Ont. : HQN Books, 2009)
When a vision of an injured Highlander appears to Tabitha Rose, she knows she's been called to help him. What Tabby doesn't expect is to be taken against her will to Black Macleod's dark, violent time.
Includes excerpt from: Dark lover (p. [371]-376).
Keywords: Teachers; Time travel; Highlands (Scotland); Love stories; Romantic suspense fiction